INDUSTRIAL RELATIONS RESEARCH IN BRITAIN - Winchester, David (British journal of industrial relations, 1983)
Despite the inherent difficulties of any review of UK industrial relations research, a simplified subject classification was developed for a brief consideration of recent research under the broad categories of trade unions, management, collective bargaining, and the state. Within these categories, there have been changing disciplinary contributions of the primary social science disciplines, as well as different research orientations. Research on trade unions has benefited from a wider variety of research orientations and a wider analytical focus. The most significant advances in management research have come from abstract reasoning and a better conceptualization of the problems. The availability of more dependable information on earnings, collective bargaining structure, and union membership will likely generate more extensive quantitative analysis in this area, but it is not certain that this will result in more convincing theoretical explanations. Increasing state intervention in industrial relations in recent years has resulted in a significant redirection of industrial relations research and teaching. The current political and economic atmosphere offers an unfriendly environment for industrial relations researchers trying to influence policymakers.